Hydrothermal rare earth elements mineralization in the Barra do Itapirapua carbonatite, southern Brazil: behaviour of selected trace elements and stable isotopes (C, O) - Andrade, FRD; Moller, P.; Luders, V; Dulski, P.; Gilg, H. A. (Elsevier B.V., 1999)
The Bura do Itapira pua carbonatite is located in southern Brazil and belongs to the Cretaceous Ponta Grossa alkaline-carbonatitic province related to the opening of the South Atlantic. The carbonatite complex is emplaced in Proterozoic granites and is mainly composed of plutonic magnesio- to ferrocarbonatite, with smaller amounts of subvolcanic magnesiocarbonatite. Hydrothermal alteration of the carbonatite has led to the formation of quartz, apatite, fluorite, rue earth fluorocarbonates, barite and sulfides in variable proportions. Trace element data, delta(13)C and delta(18)O are presented here, with the aim of better understanding the geochemical nature of hydrothermal alteration related to rare earth elements (REE) mineralization. The non-overprinted plutonic carbonatite shows the lowest REE contents, and its primitive carbon and oxygen stable isotopic composition places it in the field of primary igneous carbonatites. Two types of hydrothermally overprinted plutonic carbonatites can be distinguished based on secondary minerals and geochemical composition. Type I contains mainly quartz, rare earth fluorocarbonates and apatite as hydrothermal secondary minerals, and has steep chondrite normalized REE patterns, with Sigma(REE+Y) of up to 3 wt.% (i.e., two orders of magnitude higher than in fresh plutonic samples). In contrast, the Type II overprint contains apatite, fluorite and barite as dominant hydrothermal minerals, and is characterized by heavy REE enrichment relative to the fresh samples, with flat chondrite normalized REE patterns. Carbon and oxygen stable isotope ratios of Types I and II are elevated (delta(18)O + 8 to + 12 parts per thousand; delta(13)C - 6 to - 2 parts per thousand) relative to the fresh samples. Hydrothermally overprinted carbonatites exposed to weathering show even higher delta(18)O values (delta(18)O 13 to 25 parts per thousand) but no additional REE enrichment. The subvolcanic carbonatite has anomalously high delta(13)C of up to + 1 parts per thousand, which suggests crustal contamination through interaction with carbonate-bearing metasediments. (C) 1999 Elsevier B.V. B.V. All rights reserved.
Keywords: carbonatite; trace elements; stable isotopes; hydrothermal alteration; REE mineralization